Teaching English Vocabulary Mediated By Song - Marwan, Antika Sari; Narulita, Nita Sari; Ruslan, Ruslan (Universitas Siliwangi, 2025)
This research aims to determine the development of English word pronunciation and meaning through songs. The research method used is action research. Observation was used to collect data. Meanwhile, the data source in this study is a child approximately 9 years old. The data obtained from this study consists of observation results that have been transcribed. After all data were collected, thematic analysis by Braun Clarke (2006) was used to analyze the data. The results of the study show that the development of English word pronunciation and meaning through songs improves by pronouncing English words, singing the learned songs, understanding word meanings by answering provided questions, and learning meanings through physical activities. From the results, the researcher concludes that the use of songs in the learning process is very effective and positively influences the learning of word pronunciation and understanding of English vocabulary.